PENGARUH PENGGUNAAN ENDORSEMENT TERHADAP MINAT BELI KONSUMEN PADA AISYKOTA BIMA - Mizwar Mizwar; Muhajirin - - (Jurnal Ilmiah Satyagraha, 2021)
Satisfying consumer needs is the desire of every company. Apart from being an important factor for the survival of the company, satisfying consumer needs can increase its superiority in the competition. Consumers who are satisfied with products and services tend to repurchase the product and reuse the service when the same need reappears in the future. This study aims to determine the effect of the use of endorsements on consumer buying interest at AISY Bima city. This study uses a quantitative approach with a survey method. The population in this study are consumers who have seen endorsements that promote AISY products, the number of samples taken in this study were 50 respondents with the sampling used in this study was purposive sampling. The research instrument used a questionnaire with a Likert scale. Data analysis used simple linear regression, partial test with t test. To test the effect between variables using SPSS (Statistical Service Product Solutions) version 23.00. The results showed that endorsement had a positive and significant effect on buying interest at AISY in Bima city.